Aberrant microRNA expression in B lymphocytes from patients with primary warm autoimmune haemolytic anaemia. (4th July 2021) - Zhao, Manjun; He, Xin; Yang, Jin; Feng, Yingying; Wang, Huaquan; Shao, Zonghong; Xing, Limin
Abstract: Objective: To screen and analyze the micro-Ribonucleic Acid (miRNA) expression profile in B lymphocytes from patients with autoimmune haemolytic anaemia (AIHA) using high-throughput sequencing. Methods: Twelve patients with warm autoimmune haemolytic anaemia (wAIHA) and twelve healthy controls (HCs) were enrolled. CD19 + B lymphocytes were isolated and purified using magnetic activated cell sorting (MACS). RNA was subsequently extracted from these cells and a small RNA library was created. The miRNA expression profile was analyzed using Beijing Genomics Institute Sequencing 500 (BGISEQ-500), and stem-loop real-time quantitative PCR (stem-loop qRT-PCR) was used to verify the sequencing results. Downstream target genes of the differentially expressed miRNAs were predicted using miRanda and TargetScan online software, and GO functional enrichment and pathway enrichment analyses were performed on these genes. Results: Compared with HCs, 178 upregulated and 143 downregulated miRNAs were identified in wAIHA patients, and stem-loop qRT-PCR of four randomly selected differentially expressed miRNAs verified the sequencing results. Ninety-five significantly enriched GO terms and eighty-five significantly enriched pathways were identified. Genes targeted by differentially expressed miRNAs were found to be mainly involved in the regulation of signal transduction, metabolic processes, immune reactions, and neoplastic disease development. Conclusion: The expression of miRNAs in B lymphocytes from patients with primary wAIHA was deregulated, and this phenomenon may be involved in the pathogenesis of wAIHA.